Reduced graphene oxide, preparation method and application thereof, and supercapacitor

CN123002834APending Publication Date: 2026-10-30JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611424329.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

如现有氧化石墨烯的制备原料多为鳞片石墨或石墨粉,采用改进的Hummers法制备氧化石墨,用纯水稀释氧化产物,经超声、振荡或强力搅拌处理,得氧化石墨烯酸液,再将氧化石墨烯酸液加入还原性铁粉,制得的石墨烯粉体作为电极材料制得的电容器存在倍率性能和循环稳定性差的问题

Benefits of technology

本发明通过以可膨胀石墨替代传统的鳞片石墨或者石墨粉作为原料,并通过调控还原铁粉用量,调控所得还原氧化石墨烯的还原程度、缺陷特征及孔结构参数,进而提高以还原氧化石墨烯作为电极材料制得的电容器的倍率性能和循环稳定性,所述铁粉与可膨胀石墨的质量比为4~12:1有助于提高脱氧程度,并对片层褶皱、缺陷以及介孔结构产生调节作用,从而改善电子传输和电解液离子扩散条件,避免了过量铁粉用量造成的还原程度和孔结构的改善趋于有限,电化学性能不会继续提高的问题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123002834A_ABST
    Figure CN123002834A_ABST
Patent Text Reader

Abstract

The application provides a reduced graphene oxide, a preparation method and application thereof, and a super capacitor, and belongs to the technical field of graphite materials and electrochemical energy storage. The application uses expandable graphite as raw material, and adopts a chemical oxidation method to prepare graphene oxide water dispersion liquid; iron powder is added into the graphene oxide water dispersion liquid to perform an in-situ reduction reaction, so that the reduced graphene oxide is obtained; the mass ratio of the iron powder to the expandable graphite is 4-12:1, calculated by 1 part of the graphene oxide water dispersion liquid prepared from the expandable graphite. The application uses the expandable graphite to replace traditional flake graphite or graphite powder as raw material, and adjusts the amount of the reduced iron powder to adjust the reduction degree, defect characteristics and pore structure parameters of the obtained reduced graphene oxide, so that the rate performance and cycle stability of the capacitor prepared by using the reduced graphene oxide as electrode material are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the fields of graphite materials and electrochemical energy storage technology, and particularly to a reduced graphene oxide, its preparation method and application, and supercapacitors. Background Technology

[0002] Reduced graphene oxide is a graphene-based carbon material obtained by reducing graphene oxide. It has good electrical conductivity, high specific surface area and good structural stability, and has broad application prospects in fields such as supercapacitor electrode materials.

[0003] Traditional methods for preparing reduced graphene oxide typically involve first preparing graphene oxide and then reducing it with a chemical reducing agent to remove oxygen-containing functional groups and recover some sps. 2 The carbon skeleton structure improves the conductivity and electrochemical performance of the material. For example, the raw materials for preparing graphene oxide are mostly flake graphite or graphite powder. A modified Hummers method is used to prepare graphene oxide by diluting the oxidation product with pure water and then subjecting it to ultrasonication, oscillation, or vigorous stirring to obtain an acidic solution of graphene oxide. This solution is then mixed with reducing iron powder to produce graphene powder. Capacitors made from this graphene powder as electrode materials suffer from poor rate performance and cycle stability. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide reduced graphene oxide, its preparation method and application, and a supercapacitor. The reduced graphene oxide prepared by this invention, when used as an electrode material, produces capacitors with good rate performance and cycle stability.

[0005] To achieve the above-mentioned objectives, the present invention provides the following technical solution: This invention provides a method for preparing reduced graphene oxide (rGO), comprising the following steps: Aqueous dispersions of graphene oxide were prepared using expandable graphite (EG) as raw material via chemical oxidation. Iron powder was added to the aqueous dispersion of graphene oxide to carry out an in-situ reduction reaction to obtain the reduced graphene oxide. Based on 1 part by mass of the graphene oxide aqueous dispersion prepared from the expandable graphite, the mass ratio of the iron powder to the expandable graphite is 4~12:1.

[0006] Preferably, the mass ratio of the iron powder to the expandable graphite is 10:1.

[0007] Preferably, the iron powder is added to the graphene oxide aqueous dispersion in three separate portions.

[0008] Preferably, the temperature of the in-situ reduction reaction is 20~25℃.

[0009] Preferably, the chemical oxidation method uses a concentrated sulfuric acid-potassium persulfate oxidation system.

[0010] The present invention also provides reduced graphene oxide prepared by the preparation method described in the above technical solution.

[0011] This invention also provides the application of the reduced graphene oxide described in the above technical solution in the field of supercapacitors.

[0012] The present invention also provides a supercapacitor comprising the reduced graphene oxide described in the above technical solution.

[0013] Preferably, the supercapacitor is a symmetrical aqueous supercapacitor, and both the positive and negative electrodes of the supercapacitor contain the reduced graphene oxide.

[0014] Preferably, the electrolyte of the supercapacitor is a 6M KOH aqueous solution.

[0015] This invention provides a method for preparing reduced graphene oxide, comprising the following steps: using expandable graphite as raw material, preparing an aqueous dispersion of graphene oxide by chemical oxidation; adding iron powder to the aqueous dispersion of graphene oxide to carry out an in-situ reduction reaction to obtain the reduced graphene oxide; based on 1 part by mass of the aqueous dispersion of graphene oxide prepared from expandable graphite, the mass ratio of iron powder to expandable graphite is 4~12:1.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention improves the rate performance and cycle stability of capacitors made with reduced graphene oxide as electrode material by replacing traditional flake graphite or graphite powder with expandable graphite and by controlling the amount of reduced iron powder, thereby regulating the degree of reduction, defect characteristics, and pore structure parameters of the resulting reduced graphene oxide. The mass ratio of iron powder to expandable graphite is 4~12:1, which helps to improve the degree of deoxidation and regulates the lamellar wrinkles, defects, and mesoporous structure, thereby improving electron transport and electrolyte ion diffusion conditions. This avoids the problem that the improvement in the degree of reduction and pore structure is limited due to excessive iron powder, and the electrochemical performance will not continue to improve.

[0017] Furthermore, the chemical oxidation method described in this invention employs a concentrated sulfuric acid-potassium persulfate oxidation system. The relatively loose interlayer structure of expandable graphite facilitates the entry of acid and oxidant into the interlayer, promoting subsequent oxidation and sheet exfoliation. Iron powder, in an acidic aqueous dispersion system, can donate electrons, causing the removal of some oxygen-containing functional groups on the surface of graphene oxide and the exfoliation of some sp... 2The conjugated carbon structure is restored, and expandable graphite is used as raw material. The oxidation treatment with potassium persulfate helps to shorten the reaction time for the preparation of graphene oxide and simplify the precursor preparation process.

[0018] The results of the examples show that when the amount of reduced iron powder is increased from 4g to 10g, the degree of reduction of the obtained reduced graphene oxide is improved, the oxygen-containing functional groups are continuously reduced, and a connected pore structure dominated by 2-6nm mesopores is formed. When the amount of reduced iron powder is further increased to 12g, the structural regulation gain of the material tends to be limited. The reduced graphene oxide prepared using 10g of reduced iron powder exhibits the best electrochemical performance: in the three-electrode system, the specific capacitance reaches 251.4F / g at 1A / g, and the capacitance retention rate is 71.73% at 50A / g. The symmetrical supercapacitor obtained by further assembly still maintains 88.40% capacitance retention rate after 20,000 cycles at 20A / g, showing good rate performance and cycle stability. This invention provides a simple, green, and effective technical approach for the preparation of high-performance graphene-based supercapacitor electrode materials. Attached Figure Description

[0019] Figure 1 SEM images of expandable graphite and graphene oxide prepared in Examples 1-5 are shown, where a-f are expandable graphite and rGO prepared in Examples 1-5, respectively. Figure 2 The XRD spectra of expandable graphite and reduced graphene oxide prepared in Examples 1-5 are shown. Figure 3 XPS full spectrum of expandable graphite and graphene oxide prepared in Examples 1-5; Figure 4 Cyclic voltammetry curves of the reduced graphene oxide electrodes prepared in Examples 1-5 of the three-electrode system are shown. Figure 5 The constant current charge-discharge curves of the reduced graphene oxide electrodes prepared in Examples 1-5 of the three-electrode system are shown. Figure 6 The graphs show the specific capacitance retention rates of the reduced graphene oxide electrodes prepared in Examples 1-5 of the three-electrode system at different current densities. Figure 7 Electrochemical impedance spectroscopy (EIS) spectra of the reduced graphene oxide electrodes prepared in Examples 1-5 of the three-electrode system; Figure 8 The cycling stability curve of the reduced graphene oxide electrode prepared in Example 4 in the three-electrode system is shown. Figure 9The constant current charge-discharge curves of the symmetrical supercapacitor assembled using the reduced graphene oxide prepared in Example 4 in a dual-electrode system are shown. Figure 10 The graph shows the cycle stability of the symmetrical supercapacitor assembled using the reduced graphene oxide prepared in Example 4 in a dual-electrode system. Figure 11 The attached figures show the nitrogen adsorption-desorption of the reduced graphene oxide prepared in Examples 1-5, where a is the adsorption-desorption isotherm and b is the pore size distribution curve. Figure 12 The constant current charge-discharge curves of the symmetrical supercapacitor assembled using reduced graphene oxide prepared in Comparative Example 1 in a dual-electrode system are shown. Figure 13 The specific capacitance curve of the reduced graphene oxide electrode of Comparative Example 1 at 50 A / g is shown. Figure 14 The image shows the cycle stability curves of the symmetric supercapacitor assembled using reduced graphene oxide prepared in Comparative Example 1 in a dual-electrode system. Figure 15 The constant current charge-discharge curves of the symmetrical supercapacitor assembled using reduced graphene oxide prepared in Comparative Example 2 in the dual-electrode system are shown. Figure 16 The specific capacitance curve of the reduced graphene oxide electrode of Comparative Example 2 at 50 A / g is shown. Figure 17 The graph shows the cycle stability of the symmetrical supercapacitor assembled using reduced graphene oxide prepared in Comparative Example 2 in a dual-electrode system. Detailed Implementation

[0020] This invention provides a method for preparing reduced graphene oxide, comprising the following steps: Aqueous dispersions of graphene oxide were prepared using expandable graphite as raw material via chemical oxidation. Iron powder was added to the aqueous dispersion of graphene oxide to carry out an in-situ reduction reaction to obtain the reduced graphene oxide. Based on 1 part by mass of the graphene oxide aqueous dispersion prepared from the expandable graphite, the mass ratio of the iron powder to the expandable graphite is 4~12:1.

[0021] Unless otherwise specified, all raw materials used in this invention are commercially available products in the field.

[0022] This invention uses expandable graphite as raw material and employs a chemical oxidation method to prepare an aqueous dispersion of graphene oxide.

[0023] In this invention, the expandable graphite is a product obtained by preliminary oxidation treatment of flake graphite, in which its interlayer structure has been opened to a certain extent. The expandable graphite has a multi-layer stacked structure and is partially oxidized flake graphite.

[0024] In this invention, the chemical oxidation method preferably uses a concentrated sulfuric acid-potassium persulfate oxidation system.

[0025] In this invention, the chemical oxidation method preferably includes the following steps: Measure 25 mL of concentrated sulfuric acid (98 wt%) into a beaker, add 1 g of expandable graphite, and stir at 600 r / min for 5 min. Then, while stirring at 600 r / min, add 5 g of potassium persulfate in three equal portions by mass. Place the beaker in a 50 °C water bath and continue the reaction for 1.5 h. Next, add 50 mL of deionized water dropwise, then transfer the beaker to a 100 °C water bath and continue the reaction for 0.5 h. Finally, remove the beaker, cool it to room temperature, add 50 mL of deionized water and 5 mL of H2O2 to terminate the reaction, and obtain the graphene oxide aqueous dispersion, which can be directly used for subsequent preparations without further processing.

[0026] After obtaining the graphene oxide aqueous dispersion, the present invention adds iron powder to the graphene oxide aqueous dispersion to carry out an in-situ reduction reaction to obtain the reduced graphene oxide; based on 1 part by mass of the graphene oxide aqueous dispersion prepared from the expandable graphite, the mass ratio of the iron powder to the expandable graphite is 4~12:1.

[0027] In this invention, the preferred mass ratio of iron powder to expandable graphite is 4:1, 6:1, 8:1, 10:1 or 12:1.

[0028] In this invention, the iron powder is preferably added to the graphene oxide aqueous dispersion in three equal parts, more preferably in three equal parts by mass.

[0029] In this invention, the temperature of the in-situ reduction reaction is preferably 20~25°C, and more preferably room temperature.

[0030] In this invention, the in-situ reduction reaction is preferably carried out under stirring conditions of 600 r / min for a time of 1.5 h. During the in-situ reduction reaction, a large number of bubbles are generated in the system, resulting in a black viscous solution.

[0031] In this invention, when the iron powder undergoes an in-situ reduction reaction in a graphene oxide aqueous dispersion system, it can effectively remove some oxygen-containing functional groups on the surface of graphene oxide and restore some sp... 2The carbon skeleton structure improves the conductivity of the material. Meanwhile, as the amount of reduced iron powder increases, the surface undulation of the resulting reduced graphene oxide sheets gradually increases, the wrinkles and curling features become more obvious, and a mesoporous interconnected pore structure is formed, which is conducive to the transport and diffusion of electrolyte ions. When the amount of iron powder is too high, the gain of material structure regulation tends to be limited.

[0032] In this invention, after the in-situ reduction reaction is completed, the black viscous solution is preferably washed, filtered and dried in sequence to obtain the reduced graphene oxide.

[0033] In this invention, the washing is preferably performed by sequentially washing with water and acid washing. The number of times the water washing is performed is preferably 2. The water washing is preferably performed by centrifuging the reaction product with deionized water. The centrifugation speed is preferably 9000 r / min, and the centrifugation time is preferably 5 min each time. The number of times the acid washing is performed is preferably 2. The washing agent for the acid washing is preferably a 5 wt% hydrochloric acid solution. The acid washing process is preferably supplemented by centrifugation. The centrifugation speed is preferably 9000 r / min, and the centrifugation time is preferably 5 min each time.

[0034] In this invention, the water washing is preferably followed by vacuum filtration, and then acid washing.

[0035] In this invention, the filtration is preferably a pressure-reducing filtration.

[0036] In this invention, the drying is preferably vacuum drying, the drying temperature is preferably 100°C, and the drying time is preferably 3 hours.

[0037] The present invention also provides reduced graphene oxide prepared by the preparation method described in the above technical solution.

[0038] This invention also provides the application of the reduced graphene oxide described in the above technical solution in the field of supercapacitors.

[0039] The present invention also provides a supercapacitor comprising the reduced graphene oxide described in the above technical solution.

[0040] In this invention, the supercapacitor is preferably a symmetrical aqueous supercapacitor, and both the positive and negative electrodes of the supercapacitor preferably contain the reduced graphene oxide.

[0041] In this invention, the electrolyte of the supercapacitor is preferably a 6M KOH aqueous solution.

[0042] In this invention, the method for preparing the electrode material of the supercapacitor preferably includes the following steps: The reduced graphene oxide, conductive agent, and polytetrafluoroethylene are mixed in a mass ratio of 8:1:1 and loaded onto a current collector to obtain the electrode material.

[0043] In this invention, the current collector is preferably nickel foam.

[0044] In this invention, the conductive agent is preferably carbon black; the binder is preferably polytetrafluoroethylene.

[0045] In this invention, the preferred loading of reduced graphene oxide in the electrode material is 2 mg / cm³. 2 .

[0046] The present invention preferably employs a three-electrode system to test the electrochemical performance of the electrode material prepared by the reduced graphene oxide. The reference electrode of the three-electrode system is preferably a mercury-mercury oxide electrode, the counter electrode is preferably a platinum electrode, and the electrolyte is preferably a 6MKOH aqueous solution.

[0047] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.

[0048] Example 1 25 mL of concentrated sulfuric acid (98 wt%) was placed in a 250 mL beaker, and 1 g of expandable graphite was added. The mixture was stirred at 600 rpm for 5 min. Then, 5 g of potassium persulfate was added in three equal portions at 600 rpm. The beaker was then placed in a 50 °C water bath and the reaction continued for 1.5 h. Next, 50 mL of deionized water was added dropwise, and the beaker was transferred to a 100 °C water bath and the reaction continued for 0.5 h. After the reaction was completed, the beaker was cooled to room temperature, and 50 mL of deionized water and 5 mL of H2O2 were added to terminate the reaction, yielding an aqueous dispersion of graphene oxide.

[0049] 4g of iron powder was weighed and added to the graphene oxide aqueous dispersion in three equal portions by mass. The mixture was stirred at 600r / min for 1.5h. During this process, a large number of bubbles were generated in the system. After the reaction was completed, a black viscous solution was obtained. The solution was washed twice by centrifugation with deionized water at 9000r / min for 5min each time, and then filtered under reduced pressure. The solution was then washed twice with 5wt% hydrochloric acid, with centrifugation at 9000r / min for 5min each time, and finally filtered under reduced pressure. The obtained product was dried under vacuum at 110℃ for 3h to obtain reduced graphene oxide, denoted as rGO(4).

[0050] Example 2 Reduced graphene oxide was prepared according to the method in Example 1, except that the mass of reduced iron powder added to the graphene oxide aqueous dispersion was 6g, and the resulting sample was denoted as rGO(6).

[0051] Example 3 Reduced graphene oxide was prepared according to the method in Example 1, except that the mass of reduced iron powder added to the graphene oxide aqueous dispersion was 8g, and the resulting sample was denoted as rGO(8).

[0052] Example 4 Reduced graphene oxide was prepared according to the method in Example 1, except that the mass of reduced iron powder added to the graphene oxide aqueous dispersion was 10 g, and the resulting sample was denoted as rGO(10).

[0053] Example 5 Reduced graphene oxide was prepared according to the method in Example 1, except that the mass of reduced iron powder added to the graphene oxide aqueous dispersion was 12 g, and the resulting sample was denoted as rGO(12).

[0054] Test case 1. Characterization and morphology testing Figure 1 SEM images of expandable graphite and reduced graphene oxide prepared in Examples 1-5 are shown, where a-f represent expandable graphite and rGO prepared in Examples 1-5, respectively. It can be seen that expandable graphite forms a distinct multilayered structure with thicker and denser sheets. After chemical oxidation and in-situ reduction treatment, the resulting reduced graphene oxide samples become thinner two-dimensional layered structures. The reduced graphene oxide prepared in Examples 1-5 all exhibit typical two-dimensional sheet stacking morphology. With increasing amounts of reduced iron powder, the surface undulations of the sheets gradually increase, and the wrinkles and curling characteristics become more pronounced. When the amount of reduced iron powder is further increased to 12g, the degree of sheet wrinkling is slightly reduced compared to the sample prepared under the 10g condition.

[0055] The nitrogen adsorption-desorption figures for the reduced graphene oxide prepared in Examples 1-5 are shown in the attached figures. Figure 11 As shown in the figure, where a is the adsorption-desorption isotherm diagram and b is the pore size distribution curve, it can be seen that the specific surface area of ​​rGO(4) is 232.13 m². 2 / g, with an average pore size of 3.49nm and a pore volume of 0.27cm³. 3 The specific surface area of ​​rGO(6) is 257.48 m² / g. 2 / g, with an average pore size of 3.48nm and a pore volume of 0.29cm³. 3 The specific surface area of ​​rGO(8) is 285.29 m² / g. 2 / g, with an average pore size of 3.48nm and a pore volume of 0.32cm³. 3 The specific surface area of ​​rGO(10) is 317.82 m² / g. 2 / g, with an average pore size of 3.46nm and a pore volume of 0.36cm³. 3 / g, the pore structure is mainly 2~6nm mesopores, and the specific surface area of ​​rGO(12) is 297.57m². 2 / g, with an average pore size of 3.47nm and a pore volume of 0.33cm³. 3 / g.

[0056] Figure 2 The XRD patterns are of expandable graphite and reduced graphene oxide prepared in Examples 1-5. It can be seen that the expandable graphite exhibits a significant conductivity peak at 2θ≈26°. After chemical oxidation and in-situ reduction treatment, the conductivity characteristics of each sample changed. The rGO(4) prepared in Example 1 still shows graphene oxide-related peaks in the low-angle region, indicating that the sample reduction was insufficient under low iron powder conditions. As the amount of reduced iron powder increased, the characteristic peaks of the other samples near 2θ≈24° gradually increased, indicating that the degree of graphene oxide reduction gradually improved.

[0057] Figure 3 The XPS full spectra of expandable graphite and reduced graphene oxide prepared in Examples 1-5 are shown. It can be seen that the expandable graphite and the samples from each example are mainly composed of carbon and oxygen. Compared with the samples prepared in Examples 1-5, the oxygen characteristic peak of the expandable graphite is stronger, indicating a higher degree of oxidation. For the reduced graphene oxide samples prepared in Examples 1-5, as the amount of reduced iron powder increased, the relative carbon content in the samples gradually increased, while the oxygen content decreased accordingly, indicating that the oxygen-containing functional groups gradually decreased and the degree of reduction continuously improved. Among them, the change in elemental composition of the samples under the conditions of 10g and 12g decreased, indicating that the effect of excessive iron powder on improving the degree of reduction tended to be limited. When the amount of iron powder increased from 4g to 10g, the carbon content of the obtained material increased from 79.42wt% to 86.34wt%, and the oxygen content decreased from 19.43wt% to 12.92wt%. After further increasing to 12g, the carbon content was 86.93wt% and the oxygen content was 12.14wt%, indicating that the effect of further deoxidation after the amount of iron powder exceeded 10g tended to be limited.

[0058] 2. Electrochemical performance testing The reduced graphene oxide prepared in Examples 1-5 was used as the active material, and mixed with carbon black and polytetrafluoroethylene at a mass ratio of 8:1:1, then pressed onto a nickel foam current collector to prepare working electrodes. Each working electrode had an active material loading of 2 mg and a geometric area of ​​1 cm². 2Using a mercury-mercury oxide electrode as the reference electrode, a platinum electrode as the counter electrode, and 6MKOH aqueous solution as the electrolyte, cyclic voltammetry, constant current charge-discharge, and electrochemical impedance spectroscopy were performed in a three-electrode system. Table 1 shows the specific capacitance and rate performance test results of the reduced graphene oxide electrodes in Examples 1-5.

[0059] Table 1. Test results of specific capacitance and rate performance of the reduced graphene oxide electrodes in Examples 1-5.

[0060] In Example 4, rGO(10) exhibited high specific capacitance at 1, 2, 5, 10, 20 and 50 A / g, and maintained 71.73% of its initial specific capacitance at 50 A / g, demonstrating excellent rate performance.

[0061] Figure 4 The cyclic voltammetry curves of the reduced graphene oxide electrodes prepared in Examples 1-5 are shown in the three-electrode system at a scan rate of 50 mV / s. It can be seen that, under the same conditions, the cyclic voltammetry curve of the sample prepared in Example 4 has the largest enclosed area, indicating that it has a higher charge storage capacity; among them, the cyclic voltammetry curves of rGO(8), rGO(10), and rGO(12) are slightly distorted quasi-rectangular with weak hump characteristics, indicating that their energy storage behavior is mainly based on the electric double-layer capacitance, while a small amount of pseudocapacitance contributes.

[0062] Figure 5 The graphs show the constant current charge-discharge curves of the reduced graphene oxide electrodes prepared in Examples 1-5 at a current density of 1 A / g in a three-electrode system. It can be seen that all samples exhibit approximately linear and symmetrical charge-discharge characteristics, indicating that they mainly exhibit typical electric double-layer capacitance behavior; among them, the sample prepared in Example 4 has the longest discharge time and the highest specific capacitance.

[0063] Figure 6 The graphs show the specific capacitance retention rates of the reduced graphene oxide electrodes prepared in Examples 1-5 of the three-electrode system under different current densities. It can be seen that the specific capacitance of all samples decreases with increasing current density, but the sample prepared in Example 4 maintains a high specific capacitance and excellent retention rate under high current density conditions, indicating that it has the best rate performance.

[0064] Figure 7 The images show the electrochemical impedance spectroscopy (EIS) spectra of the reduced graphene oxide electrodes prepared in Examples 1-5 of the three-electrode system, with insets showing partial magnifications. It can be seen that the sample prepared in Example 4 has the smallest semicircular diameter in the high-frequency region and a larger slope in the low-frequency region, indicating lower charge transfer resistance and stronger ion diffusion and migration capabilities.

[0065] From Table 1 and Figures 4-7It can be seen that as the amount of iron powder increases, the electrochemical performance of the resulting reduced graphene oxide electrode generally shows a trend of first increasing and then slightly decreasing. Among them, the rGO(10) prepared in Example 4 has the best electrochemical performance. The reason is that appropriately increasing the amount of reduced iron powder can improve the degree of reduction of graphene oxide, reduce oxygen-containing functional groups, enhance the lamellar wrinkles and defect features, and form a pore structure that is more conducive to ion transport; however, when the amount of iron powder continues to increase, the gain of material structure regulation tends to be limited, so the performance no longer continues to improve.

[0066] Figure 8 The graph shows the cycling stability of the reduced graphene oxide electrode prepared in Example 4 of the three-electrode system. It can be seen that after 10,000 cycles at 20 A / g, the specific capacitance of the sample prepared in Example 4 remains at a high level, indicating that the material has good cycling stability.

[0067] Furthermore, the rGO(10) prepared in Example 4 was used as the positive and negative electrode materials to assemble a symmetrical supercapacitor, 6MKOH aqueous solution was used as the electrolyte, and electrochemical tests were performed in the two-electrode system. Figure 9 The image shows the constant current charge-discharge curves of the symmetrical supercapacitor assembled using the reduced graphene oxide prepared in Example 4 within a dual-electrode system. It can be seen that the constant current charge-discharge curves of this device exhibit good symmetry and a small voltage drop. Figure 10 The graph shows the cycling stability of the symmetrical supercapacitor assembled using the reduced graphene oxide prepared in Example 4 in a dual-electrode system. It can be seen that after 20,000 cycles at 20 A / g, its specific capacitance retention rate still reaches 88.40%, indicating that this symmetrical supercapacitor has good cycling stability.

[0068] In summary, through Examples 1-5 and their electrochemical test results, it can be found that the reduced graphene oxide prepared by the iron powder in-situ reduction method of the present invention can achieve structural and performance optimization by adjusting the amount of reduced iron powder. Among them, the rGO(10) prepared in Example 4 has high specific capacitance, excellent rate performance and good cycle stability, and has good application prospects in the field of electrode materials for aqueous supercapacitors.

[0069] Comparative Example 1 Same as Example 4, except that expandable graphite is replaced with flake graphite.

[0070] Electrochemical performance was tested using the same testing methods as in Examples 1-5. In the three-electrode system, the specific capacitances of the prepared samples at 1, 2, 5, 10, 20 and 50 A / g were 199.13, 185.42, 155.50, 140.10, 130.20 and 119.50 F / g, respectively, and the samples still retained 60.01% of the initial specific capacitance at 50 A / g. Figure 13 The specific capacitance curve of the reduced graphene oxide electrode of Comparative Example 1 at 50 A / g is shown.

[0071] The reduced graphene oxide prepared in Comparative Example 1 was used as the positive and negative electrode materials to assemble a symmetrical supercapacitor, with 6MKOH aqueous solution as the electrolyte, and electrochemical tests were performed in the two-electrode system. Figure 12 The constant current charge-discharge curves are shown for the symmetrical supercapacitor assembled using reduced graphene oxide prepared in Comparative Example 1 in a dual-electrode system. Figure 14 The graph shows the cycling stability of the symmetrical supercapacitor assembled using reduced graphene oxide prepared in Comparative Example 1 in a dual-electrode system. It can be seen that after 20,000 cycles at 20 A / g, its specific capacitance retention is only 77.04%, and its cycling stability is lower than that of the example.

[0072] Comparative Example 2 Same as Example 4, except that expandable graphite is replaced with graphite powder.

[0073] Electrochemical performance was tested using the same testing methods as in Examples 1-5. In the three-electrode system, the specific capacitances of the prepared samples at 1, 2, 5, 10, 20 and 50 A / g were 210.32, 198.64, 185.50, 169.40, 152.20 and 132.50 F / g, respectively, and they still maintained 63.01% of the initial specific capacitance at 50 A / g. Figure 16 The specific capacitance curve of the reduced graphene oxide electrode of Comparative Example 2 at 50 A / g is shown.

[0074] The reduced graphene oxide prepared in Comparative Example 2 was used as the positive and negative electrode materials to assemble a symmetrical supercapacitor, with 6MKOH aqueous solution as the electrolyte, and electrochemical tests were performed in the two-electrode system. Figure 15 The constant current charge-discharge curves are shown for the symmetrical supercapacitor assembled using reduced graphene oxide prepared in Comparative Example 2 in a dual-electrode system. Figure 17 The graph shows the cycling stability of the symmetrical supercapacitor assembled using reduced graphene oxide prepared in Comparative Example 2 in a dual-electrode system. It can be seen that after 20,000 cycles at 20 A / g, its specific capacitance retention is only 79.13%, and its cycling stability is lower than that of the example.

[0075] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing reduced graphene oxide, characterized in that, Includes the following steps: Aqueous dispersions of graphene oxide were prepared using expandable graphite as raw material via chemical oxidation. Iron powder was added to the aqueous dispersion of graphene oxide to carry out an in-situ reduction reaction to obtain the reduced graphene oxide. Based on 1 part by mass of the graphene oxide aqueous dispersion prepared from the expandable graphite, the mass ratio of the iron powder to the expandable graphite is 4~12:

1.

2. The preparation method according to claim 1, characterized in that, The mass ratio of the iron powder to the expandable graphite is 10:

1.

3. The preparation method according to claim 1, characterized in that, The iron powder was added to the graphene oxide aqueous dispersion in three separate portions.

4. The preparation method according to claim 1, characterized in that, The in-situ reduction reaction is carried out at a temperature of 20~25℃.

5. The preparation method according to claim 1, characterized in that, The chemical oxidation method uses a concentrated sulfuric acid-potassium persulfate oxidation system.

6. Reduced graphene oxide prepared by the preparation method according to any one of claims 1 to 5.

7. The application of the reduced graphene oxide as described in claim 6 in the field of supercapacitors.

8. A supercapacitor, characterized in that, Includes the reduced graphene oxide as described in claim 6.

9. The supercapacitor according to claim 8, characterized in that, The supercapacitor is a symmetrical aqueous supercapacitor, and both the positive and negative electrodes of the supercapacitor contain the reduced graphene oxide.

10. The supercapacitor according to claim 8, characterized in that, The electrolyte of the supercapacitor is a 6M KOH aqueous solution.